Influence of cabbage resistance and colour upon the diamondback moth and its parasitoid Oomyzus sokolowskii. Issue 1 (18th June 2013) - Colares, Felipe; Silva‐Torres, Christian S. A.; Torres, Jorge B.; Barros, Eduardo M.; Pallini, Angelo
Abstract Host plant resistance and biological control are vital integrated pest management tools against the diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), but to date no study has investigated this system including the DBM parasitoid Oomyzus sokolowskii (Kurdjumov) (Hymenoptera: Eulophidae). We examined oviposition and development of P. xylostella exposed to two commercial cabbage cultivars (green 'Chato de quintal' and red 'Roxo') and possible effects upon O. sokolowskii. Under free‐choice tests, DBM females laid significantly more eggs on plants of the green cabbage, even though several population growth parameters showed that DBM developed better on the red cabbage. Furthermore, a laboratory free‐choice test with artificially green‐ and red‐painted kale leaf discs demonstrated a similar oviposition preference pattern, with green colour being preferred over red colour. The preference was apparently visually mediated; olfactometer tests showed similar attraction of moths to both green and red cultivars in choice and non‐choice tests. Host plant cultivar had no statistically significant effect on female parasitoid behaviour towards DBM larvae, nor on parasitoid numbers or longevity. Moreover, wasps parasitizing DBM larvae reared on the green cultivar developed more quickly and in larger numbers per parasitized larva. Thus, feeding on green cabbage rather than red does not hinder, and potentially even enhances, control of DBM by O. sokolowskii. On a practical level, these results suggest that intercalating green cabbage cultivars as a trap crop might help protect more profitable red cultivars in growing fields.